New Evidence on Altruism: A Study of TIAA-CREF Retirees - Laitner, John; Juster, F. Thomas (American Economic Review, 1996)
This paper investigates the role in household wealth accumulation of saving for bequests. It employs data from a 1988 survey of TIAA-CREF annuitants designed to measure pension and other net worth, as well as lifetime earnings. About half of the households in the data plan to leave estates, and we find that their behavior conforms with theoretical altruistic models. For the same families, the amount of wealth which we attribute to estate building is large. Nevertheless, altruism towards one's children does not seem to be the major explanation of saving in the overall sample.